Synergistic degradation of rhodamine B on BiOClxBr1−x sheets by combined photosensitization and photocatalysis under visible light irradiation1. (23rd February 2015) - Du, Dandan; Li, Wenjuan; Chen, Shasha; Yan, Tingjiang; You, Jinmao; Kong, Desheng
Abstract : The degradation of RhB was the synergistic effect of the photosensitization of RhB and photocatalysis of BiOCl x Br1− x under visible light irradiation. Abstract : BiOCl x Br1− x sheets were synthesized by a simple precipitation method. These samples showed good activities in the degradation of rhodamine B (RhB) under visible light irradiation (420 nm < λ < 800 nm). From a series of characterization techniques, the results showed that the degradation was driven by the photosensitization of RhB and photocatalysis of BiOCl x Br1− x . The mechanism of the synergistic degradation processes was explored by comparing the degradation properties of BiOCl x Br1− x (Cl : Br = 1 : 1) and BiOBr. The main active species that played important roles in the degradation process were electrons and O2 ˙ − in the BiOCl x Br1− x (Cl : Br = 1 : 1) system, while in the BiOBr system, electrons, O2 ˙ − and holes were the main active species. Such a heterogeneous synergistic degradation reaction has much significance in revealing the degradation mechanism of organic pollutants in ordinary photocatalysis.